Effects of Tylosin Administration Routes on the Development of Antimicrobial Resistance in Fecal Enterococci of Finishing Swine - F. Wu; M. D. Tokach; J. M. DeRouchey; S. S. Dritz; J. C. Woodworth; R. D. Goodband; K. Chitakasempornkul; N. M. Bello; K. Capps; S. E. Remfry; R. G. Amachawadi; T. G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 2018)
Antibiotics can be administered via various routes in pigs, which may influence antimicrobial resistance development. A total of 40 barrows and 40 gilts (Line 600 × 241; DNA, Columbus, NE; initially 207 ± 7.9 lb) were used in a 35-d trial to determine the effects of tylosin administration route on pig growth performance and development of antimicrobial resistance in fecalEnterococcusspp. isolates. Pens of pigs (1 pig/ pen, 20 pigs/treatment) were blocked by initial body weight (BW) and gender. Within blocks, pens were randomly allotted to 1 of 4 treatments. The antibiotic treatments followed US label directions and were: 1) no antibiotic (Control); 2) 110 mg tylosin per kg of feed for 21 d (Feed); 3) 8.82 mg tylosin per kg of BW through intramuscular injection twice daily for the first 3 d of each wk during the 3-wk treatment period (Injection); and 4) 66 mg of tylosin per liter of drinking water for the first 3 d of each wk during treatment period (Water). Treatments were offered during d 0 to 21, after which all pigs were fed a common diet with no antibiotic until d 35. Fecal samples were collected on d 0, 21, and 35. No evidence for route × gender interactions (P>0.55) were observed for any growth responses. From d 0 to 21, control pigs and pigs fed medicated feed had greater (P<0.05) average daily gain (ADG) than those that received injected tylosin, with the ADG of pigs receiving tylosin through the water intermediate. There was no evidence for different average daily feed intake (ADFI) among treatment groups. Pigs that received tylosin through injection or water had poorer (P<0.05) feed efficiency (F/G) compared with control pigs, but there was no evidence for difference from pigs receiving tylosin through feed. Among the medicated pigs, total tylosin dose administered was the greatest through injection, second highest through feed, with the water medication route the lowest. No evidence for route × day interactions (P>0.23) were observed for the development of bacterial resistance to any antibiotics. Enterococcal isolates collected from pigs receiving tylosin via feed or injection were more resistant (P<0.05) to erythromycin and tylosin compared with control pigs and those that received tylosin through water. The estimated probability of antimicrobial resistance to these 2 antibiotics was greater on d 21 and 35 than d 0. In summary, tylosin injection resulted in poorer ADG and F/G of finishing pigs, likely due to stress associated with handling and injection. Tylosin administration through injection and feed resulted in greater probability of enterococcal resistance to erythromycin and tylosin compared with in-water treatment, which is likely a combined effect of administration route and dosage.
Keywords: administration route; antimicrobial resistance; fecal enterococci; finishing pig; growth performance; tylosin